Physicochemical characterization, lipid-modulating effects, and proteomic insights of Malaysian Sacha Inchi (Plukenetia volubilis L.) seed oil in HepG2 cells - Fardush, Mariam; Mohd Fauzi, Norsyahida; Yan, Ho Wen; Nurdin, Armania; Jantan, Ibrahim; Nor Muhammad, Nor Azlan; Hazim, Siti Nurlisa; Mustafa, Sarmila Hanim; Feguro, Kimberlyn (Elsevier, 2025)
Sacha Inchi (SI) (Plukenetia volubilis L.) is recognized for its health benefits, especially in lipid modulation. However, its effects on lipid-metabolizing pathways at the proteomic level, particularly in hepatic models like HepG2 cells, remain underexplored. This study investigated the lipid-modulating effects of Malaysian SI seed oil on oleic acid (OA)-induced HepG2 cells, utilizing physicochemical characterization, lipid accumulation assays, proteomics, and pathway analysis. The physicochemical analysis confirmed its oxidative stability and a favorable omega-3/omega-6 ratio, supporting its nutritional potential. Oil Red O staining demonstrated concentration-dependent reductions in OA-induced lipid accumulation, with 20 μL/mL SI oil achieving efficacy comparable to atorvastatin. Proteomic and pathway analyses revealed significant modulation of key proteins (VDAC3, ALDH9A1, SOD2, GSTK1, and ACAT1) associated with lipid-related pathways. Fatty acid degradation exhibited the highest fold enrichment (48-fold, p < 0.001), while peroxisome, ferroptosis, and fat digestion/absorption pathways were also significantly enriched. These findings suggested that SI oil modulated lipid metabolism through several key lipid-related pathways, highlighting its potential as a therapeutic agent for regulating metabolism and promoting liver health. Further in vivo and clinical studies are needed to validate its therapeutic potential.